Boganmeldelser - Zila, Josef; Shannon, David; Eliassen, Anja; Melander, Sakari; Svensson, Kerstin; Mathiesen, Thomas; Tham, Henrik; Hauge, Ragnar; Tolstrup, Jens; Garde, Peter (Nordisk Tidsskrift for Kriminalvidenskab, 2005)
Book reviews